2017
DOI: 10.1159/000477901
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial Internal Carotid Artery Wall Calcification in Ischemic Strokes Treated with Thrombolysis

Abstract: Background: Calcifications are an important element of atherosclerotic plaques and have been used as a marker of atherosclerosis and clinical outcome predictor in different vascular territories. CT-scan, performed in the acute ischemic stroke setting, can reliably detect intracranial arterial calcifications. Objectives: To investigate the association between intracranial internal carotid artery calcification and functional outcome, symptomatic intracerebral hemorrhage (sICH), recanalization, and death. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 19 publications
3
20
0
Order By: Relevance
“…There are many discrepancies among other studies and ours, such as different ICAC assessment methods; e.g., both of the studies used the Total Carotid Siphon Calcification (TCSC) score (33, 34) but different inclusion and exclusion criteria. For example, Tábuas-Pereira et al (34) included patients with posterior circulation infarctions. In addition, different grouping methods were used; e.g., Lin et al (33) dichotomized patients into two groups according to TCSC scores rather than analyzing the scores as continuous variables.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…There are many discrepancies among other studies and ours, such as different ICAC assessment methods; e.g., both of the studies used the Total Carotid Siphon Calcification (TCSC) score (33, 34) but different inclusion and exclusion criteria. For example, Tábuas-Pereira et al (34) included patients with posterior circulation infarctions. In addition, different grouping methods were used; e.g., Lin et al (33) dichotomized patients into two groups according to TCSC scores rather than analyzing the scores as continuous variables.…”
Section: Discussionmentioning
confidence: 83%
“…Lin et al (33) showed that AIS patients with moderate to severe ICAC were more at risk of ICH but not sICH than patients with no or minor ICAC. In addition, Tábuas-Pereira et al (34) found that AIS patients with higher grades of ICAC have higher mortality rates following IVT. There are many discrepancies among other studies and ours, such as different ICAC assessment methods; e.g., both of the studies used the Total Carotid Siphon Calcification (TCSC) score (33, 34) but different inclusion and exclusion criteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, according to the previous epidemiological investigation, 58.1% of thrombolysis-treated patients with IS get satisfactory vascular recanalization and 5.8% patients have symptomatic intracranial hemorrhage [ 24 ]. In other words, neurological function improvement does not occur in approximately half of patients.…”
Section: Discussionmentioning
confidence: 99%
“…A plain CT scan can present the infarcted territory and provide some clues of the etiology of AIS. High-density plaques in the CT scans can be observed in patients with symptomatic ICAS, which may also be observed in patient ICAS-LVO related AIS [ 33 , 34 ]. This sign usually indicates the calcification of atherosclerotic plaque.…”
Section: Potential Methods Of Diagnosing Icas-lvomentioning
confidence: 99%